Skin immune status - live imaging of the skin in 3D - Kabashima, Kenji (Henry Stewart Talks, 2014)
Skin immunity, Immune response in the skin- Live imaging of the skin in 3D, Immune response to hapten and protein, Visualization of vascular permeability